Public finance - Rosen, Harvey S. (New York : McGraw-Hill Irwin, 2005)
"Harvey S. Rosen introduces readers to the latest research in Public Finance. With highlights from the Bush administration, updates to tax laws, and discussions of up-to-date examples, Rosen's approach encompasses important revisions to the Seventh Edition, with current changes to government policy." "Additional revisions to the Seventh Edition include new discussions regarding estate, pollution, corporate, and personal income taxes, savings issues, and corporate scandals."--BOOK JACKET.
Includes bibliographical references and indexes.
Keywords: Finance, Public -- United States